Morphogenetic Properties Of Grass-Gray Soils - Ro`ziyeva I.J; Tursunova S.A.; Chаriyeva N.N. (Zien Journals, 2022)
Origin, distribution, relief of gray oasis soils in the territory of Surkhandarya region, lithologicalgeomorphological, hydrogeological conditions of the studied area and soil-forming factors and morphological features of soils, mechanical composition, nutrient supply.
Keywords: meadow-gray soils; morphology; mechanical composition; relief